Do austerity cuts spare police budgets?: Welfare-to-carceral realignment during fiscal crises - Beck, Brenden (Criminology, 2024)
Did governments shift funding from their social welfare functions to their criminal justice functions after the 1980s? Studies investigating this possible "punitive turn" have been inconclusive and have been conducted at the state or national scale. Cities, however, are increasingly important as government responsibility devolves downward and social movements target municipal police budgets. This study contributes to ongoing academic and political debates about welfare-state retrenchment and police department funding using data on 390 U.S. cities between 1990 and 2019. In contrast to conventional explanations for budgetary restructuring that foreground across-the-board cuts or macroeconomic causes, this study proposes a fiscal crisis model that emphasizes localized budget deficits, beliefs about policing's primacy, and police agencies’ political power. Data reveal gradual and considerable municipal budgetary restructuring toward law enforcement between 1990 and 2019, with police funding growing 32% relative to social spending. Fixed-effects regression models with asymmetric predictors find that when municipal revenues fell by 10%, cities reduced police expenditures by an associated 1% and social service expenditures by 4%, with parks and housing seeing the biggest cuts. During austerity, municipalities cut police shallowly and temporarily while cutting social services deeply and enduringly, accelerating welfare-to-carceral realignment.